Developing interdisciplinary thinking in a food and nutritional security, hunger, and sustainability graduate course. Issue 1 (1st January 2020) - Knobloch, Neil A.; Charoenmuang, Mingla; Cooperstone, Jessica L.; Patil, Bhimanagouda S.
ABSTRACT: Purpose: The purpose of this study was to describe faculty and graduate students' motivation and learning experiences in a multi-institutional, interdisciplinary graduate course focused on the nexus of food and nutritional security, hunger, and sustainability. Design/Methodology/Approach: A one-group pre-experimental case study design was used. Faculty and students completed questionnaires, which included rating scales and open-ended questions. Data were analyzed and triangulated into key findings. Findings: Results indicated that faculty were interested and engaged in the development of the interdisciplinary course, and students were engaged in interdisciplinary learning and developed communication and education skills through experiential place-based learning. Practical Implications: Faculty developed a common understanding of their different disciplinary perspectives that helped provide a more cohesive and complementary interdisciplinary learning experience for students. Students learned about global challenges while identifying similar challenges in their local communities through the experiential learning assignments. Theoretical Implications: The design of the interdisciplinary course helped students think critically and creatively to learn complex issues. Advances in technology and active learning support a flipped classroom model to engage students. Place-based learning combined with interdisciplinary classroom experiences connected students to local real-world contexts and provided students with practical applications of problem-solving, critical thinking, and systems thinking skills. Originality/Value: Graduate students conducted an asset and needs assessment, which connected them to professionals in the community. Students think food and nutritional security, hunger, and sustainability are global challenges and seldom notice food insecurity in their local communities.